2015
DOI: 10.1038/srep15032
|View full text |Cite
|
Sign up to set email alerts
|

Intraperitoneal Administration of a Novel TAT-BDNF Peptide Ameliorates Cognitive Impairments via Modulating Multiple Pathways in Two Alzheimer’s Rodent Models

Abstract: Although Alzheimer’s disease (AD) has been reported for more than 100 years, there is still a lack of effective cures for this devastating disorder. Among the various obstacles that hold back drug development, the blood-brain barrier (BBB) is one of them. Here, we constructed a novel fusion peptide by linking the active domain of brain-derived neurotrophic factor (BDNF) with an HIV-encoded transactivator of transcription (TAT) that has a strong membrane-penetrating property. After intraperitoneal injection, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
32
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 52 publications
5
32
0
Order By: Relevance
“…In this study, we found that PGS32 up-regulated the phosphorylation of TrkB. It was reported that compared with the vehicle control rats, p-TrkB was significantly decreased in the scopolamine-infused rats [35] . Galantamine, a cholinergic stimulator used as a positive control, was shown to restore p-TrkB levels and improved cognitive functioning in AD-like rodent models in another study, which is inconsistent with our results.…”
Section: Discussionsupporting
confidence: 48%
“…In this study, we found that PGS32 up-regulated the phosphorylation of TrkB. It was reported that compared with the vehicle control rats, p-TrkB was significantly decreased in the scopolamine-infused rats [35] . Galantamine, a cholinergic stimulator used as a positive control, was shown to restore p-TrkB levels and improved cognitive functioning in AD-like rodent models in another study, which is inconsistent with our results.…”
Section: Discussionsupporting
confidence: 48%
“…The use of TAT as a carrier for brain delivery of drugs has been employed in several experimental approaches for the treatment of AD-like pathology in mouse models 12 13 . Recently, intraperitoneal administration of a TAT-BDNF peptide complex for 1 month was shown to improve the cognitive functions in AD rodent models 23 .…”
Section: Discussionmentioning
confidence: 99%
“…18 Other pathways activated include the mutagen activated protein kinase (Ras-MAPK) signaling which promotes neuronal differentiation, the P13 kinase-AK+ signaling which promotes survival and growth of neurons 19 and the TrKB/ ERK1/2/Ak+ pathway which significantly improves spatial memory. 20 BDNF has also been shown to activate NFkβ which enhances both dendritic spine and excitatory synapse density. 18 Impairment in spatial learning have been seen in mice lacking in NF-kβ subunit.…”
Section: Duration Of Infection 115mentioning
confidence: 99%